2015
DOI: 10.1111/jne.12290
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Visualisation of Oxytocin in the Hypothalamo‐neurohypophysial/‐spinal Pathways After Chronic Inflammation in Oxytocin‐Monomeric Red Fluorescent Protein 1 Transgenic Rats

Abstract: Oxytocin (OXT) is a well-known neurohypophysial hormone that is synthesised in the paraventricular (PVN) and supraoptic nuclei (SON) of the hypothalamus. The projection of magnocellular neurosecretory cells, which synthesise OXT and arginine vasopressin in the PVN and SON, to the posterior pituitary plays an essential role in mammalian labour and lactation through its peripheral action. However, previous studies have shown that parvocellular OXTergic cells in the PVN, which project to the medulla and spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 55 publications
3
39
0
Order By: Relevance
“…In addition, oxytocin, through effects on GABA responses in nociceptive neurons, has an analgesic effect in newborn rat pups during delivery (Mazzuca et al, 2011). There is also evidence of up-regulation of oxytocin in plasma and CNS as well as an analgesic effect in rodent models of inflammatory (Eliava et al, 2016;Matsuura et al, 2015) and neuropathic pain (Gutierrez et al, 2013).…”
Section: The Analgesic Effects Of Oxytocinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, oxytocin, through effects on GABA responses in nociceptive neurons, has an analgesic effect in newborn rat pups during delivery (Mazzuca et al, 2011). There is also evidence of up-regulation of oxytocin in plasma and CNS as well as an analgesic effect in rodent models of inflammatory (Eliava et al, 2016;Matsuura et al, 2015) and neuropathic pain (Gutierrez et al, 2013).…”
Section: The Analgesic Effects Of Oxytocinmentioning
confidence: 99%
“…Intriguingly activity of Clow threshold mechanosensitve afferents (C-LTMs) is integrated with that of nociceptors in lamina I wide dynamic range neurons (Andrew, 2010), the relevance of which will become apparent later. In models of nociceptive and inflammatory pain increased oxytocin expression and evidence of neuronal activation is seen in parvocellular PVN (Matsuura et al, 2016(Matsuura et al, , 2015. Optogenetic activation of parvocellular PVN oxytocin secreting neurons also resulted in analgesia in inflammatory although not neuropathic rodent pain models (Eliava et al, 2016).…”
Section: The Analgesic Effects Of Oxytocinmentioning
confidence: 99%
“…The method for preparing the tissue specimens with stained sections and the analysis of specimens with microscopy were performed as described previously (7,8,31). The sections were mounted on glass slides and cover-slipped using Vectashield (Vector Laboratories Co. Ltd., CA, USA).…”
Section: Fos Colocalization With Oxt/avpmentioning
confidence: 99%
“…Adjuvant arthritis is a model of poly-arthritis induced by immunogenic adjuvants (complete Freund's adjuvant) (14,15). Our previous studies with the adjuvant arthritis model showed that chronic multiple-arthritis activates the OXT/AVP system separately (7,10). Further, AVP, not corticotropinreleasing hormone (CRH), predominantly activates the HPA axis in chronic multiple-arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been identified in rats that there is significant increase in plasma OT levels at the early stage of sepsis (25), brain OT release following pancreatic injury (26), OT mRNA in adjuvant arthritis (28), and Fos expression in the OSS in advanced cancer (27). Thus, increased OT levels manifest immune disturbance.…”
Section: Immune Functions Of the Ossmentioning
confidence: 99%